The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/ijc.32178
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between IGF2‐PI3K axis and cancer‐associated‐fibroblasts promotes anal squamous carcinogenesis

Abstract: Anal squamous cell carcinoma (ASCC) is a rare tumour, but its incidence is increasing. Standard chemoradiotherapy fails to cure 20% of patients and no targeted therapy is currently approved for recurrent ASCC. The PI3K/Akt/mTOR pathway is frequently altered in this poorly characterised carcinoma. IGF2 was identified here as a key factor in ASCC oncogenesis, as IGF2 was shown to play a crucial role in the PI3K pathway with frequent (~60%) and mutually exclusive genomic alterations in IGF2, IGF1R, PTEN and PIK3C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
(59 reference statements)
0
7
0
Order By: Relevance
“… 18 , 19 The regulation of IGF2 in the PI3K/AKT/mTOR signalling pathway indicated that there might be a positive feedback loop between mTOR and IGF2BP3 expression. 20 , 21 However, the molecular mechanisms of IGF2BP3 in NPC are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 The regulation of IGF2 in the PI3K/AKT/mTOR signalling pathway indicated that there might be a positive feedback loop between mTOR and IGF2BP3 expression. 20 , 21 However, the molecular mechanisms of IGF2BP3 in NPC are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…3 ). The fact that PI3K/AKT signaling pathways regulated CAF-mediated cancer cell proliferation in oral, 136 lung, 137 , 138 gastric, 139 colon, 140 endometrial, 141 and anal 142 cancers. Mechanistically, in gastric cancer, a neutralizing antibody against Nodal attenuated CAF-induced cancer cell proliferation through Nodal-induced activation of the Smad2/3/AKT signal axis.…”
Section: Major Signaling Pathways and Targeted Therapies In Cafsmentioning
confidence: 99%
“…In this study, CAFs from primary tumours were shown to promote stemness characteristics of lung cancer-stem cells (expression of Nanog and Oct3/4), an effect which was shown to be partly dependent on the expression of IGF-II. IGF-II in CAFs is known to accelerate tumour growth in cholangiocarcinoma xenograft models 77 and promotes proliferation of anal squamous cell carcinoma cells 78 . Moreover, expression of IGF-II has been shown to promote differentiation of fibroblasts into myofibroblasts in idiopathic pulmonary fibrosis and scleroderma/systemic sclerosis-associated pulmonary fibrosis 79 .…”
Section: Cellular Procceses In Cafsmentioning
confidence: 99%